Sleep Disturbance and Physiological Regulation among Young Adults with Prior Depression - Hamilton, Jessica L. (J Psychiatr Res, 2019)
Sleep disturbance and respiratory sinus arrhythmia (RSA) are well-known to be independently associated with depression. Yet, it remains unclear how sleep disturbance and impaired physiological regulation (indexed by RSA) may synergistically contribute to depression risk. The current study examined the relationship between sleep disturbance (duration, insomnia) on daily depressive symptoms, and whether RSA moderated this relationship in a sample of young adults with a history of depression. To examine hypotheses, participants (N = 102, ages 18–22) completed a laboratory socio-evaluative stressor task to assess RSA at rest and reactivity. Participants then completed daily measures of sleep duration, insomnia symptoms, and depressive symptoms for two weeks. For main effects, multilevel modeling indicated that shorter overall sleep duration (but not insomnia) predicted higher depressive symptoms, and individual fluctuations in insomnia symptoms (but not sleep duration) predicted higher levels of next-day depressive symptoms. Lower resting RSA, but not reactivity, potentiated these relationships. Individual differences in sleep disturbance (duration and insomnia) predicted prospective levels of depressive symptoms among individuals with lower physiological regulation (indexed by lower RSA), who were particularly vulnerable to the daily effects of sleep disturbance on depressed mood. These results suggest the need to examine both daily sleep disturbance and physiological regulation to understand who may be at greatest risk for depression.